RELENDO RAWLS APÓS PIKETTY: justiça, desigualdade e democracia de cidadãos proprietários - Leandro Martins Zanitelli (Universidade Federal do Maranhão, 2015)
When discussing the type of institutional regime most prone to realizing the principles of justice as fairness, Rawls (2001) presents three arguments about the superiority of a property-owning democracy over welfare-state capitalism, concerning, respectively, the fair value of political liberties, fair equality of opportunity and the difference principle. In a critique of those arguments, O’Neill (2012) states that only the last one, the argument of the difference principle, is convincing. This paper, tries to demonstrate how Piketty’s (2014) recent analysis of the tendency of increasing inequality in low-growth societies offers support to Rawls’s arguments favoring property-owning democracy in matters regarding the fair value of political liberties and fair equality of opportunity. Piketty’s work also stresses the importance, in what refers to the difference principle, of distinguishing between a regime encompassing policies to prevent the wealth concentration (property-owning democracy) and another one whose exclusive concern is to reduce income inequality (welfare-state capitalism).